KEPUTUSAN TIDAK MENIKAH DAN TIDAK MEMILIKI ANAK DI KOREA SELATAN DIADOPSI MUSLIM SAAT INI - Nuraini, Diah (STIT Sunan Giri Bima, 2024)
This study aims to analyze the factors influencing the decision to remain unmarried, childfree, and childless within the Muslim community in South Korea, focusing on socio-demographic perspectives and Islamic legal views. South Korea's low fertility rate of 0.78 children per woman by 2022 is the main background of this research, which explores the phenomenon of changing family structures amid contemporary economic and social complexities. The research method uses a descriptive-analytical approach with data collection techniques through literature study, in-depth interviews, and document analysis from official sources such as the Organization for Economic Co-operation and Development and worldometers. Demographic and statistical data were analyzed comparatively with reference to Islamic normative perspectives. The results identified four main typologies in the family phenomenon: (1) single individuals who reject marriage due to economic and social concerns, (2) a preference for adoption over having biological children, (3) couples who experience childlessness due to procrastination, and (4) the childfree decision as a conscious choice. The study of Islamic law shows the flexibility of the four madhhabs in viewing postponement of pregnancy, provided that it does not violate reproductive and spiritual principles. The research concludes that the choice of childfree or childless is a complex response to socio-economic uncertainty, which requires mathematical planning.